MODERN TRENDS IN HEART VALVE PROSTHETICS - Aripov Dilshodbek Murodilloevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Currently, it is becoming clear that standard techniques for heart valve replacement are suboptimal. Non-physiological hemodynamics, the presence of prosthesis-dependent complications in the form of thrombosis, prosthetic endocarditis, early biodegradation are the main factors that do not allow these prostheses to be an "ideal replacement" for the affected valve. Modern operations on the aortic valve allow almost complete reproduction of the natural anatomy and give encouraging results of application. This review is devoted to the discussion of modern trends in heart valve replacement.